2021
DOI: 10.1186/s12891-020-03940-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with failure of bony union after conservative treatment of acute cases of unilateral lumbar spondylolysis

Abstract: Background If bone union is expected, conservative treatment is generally selected for lumbar spondylolysis. However, sometimes conservative treatments are unsuccessful. We sought to determine the factors associated with failure of bony union in acute unilateral lumbar spondylolysis with bone marrow edema including contralateral pseudarthrosis. Methods This study targeted unilateral lumbar spondylolysis treated conservatively in high school or youn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…Although this case was a recurrence after conservative treatment, we believe that internal fixation will eliminate the risk of recurrence and allow the patient to compete without worrying about recurrence in the future. In addition, it has been reported that the results of conservative treatment for contralateral pseudoarthrosis in bilateral lesions are very poor [20]. Therefore, we believe that internal fixation of the unilateral lesion to ensure bone union may stop the negative cycle of fractures and pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 93%
“…Although this case was a recurrence after conservative treatment, we believe that internal fixation will eliminate the risk of recurrence and allow the patient to compete without worrying about recurrence in the future. In addition, it has been reported that the results of conservative treatment for contralateral pseudoarthrosis in bilateral lesions are very poor [20]. Therefore, we believe that internal fixation of the unilateral lesion to ensure bone union may stop the negative cycle of fractures and pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 93%
“…6 in our study, the bone union rate and the treatment period did not differ so much between adolescents and adults. In a previous study 16) , patients with bilateral acute spondylolysis were excluded, and some patients exhibited pseudarthrosis lesions on the contralateral side, which negatively impacts bone union [17][18][19] ; these factors prevent simple comparisons between these studies. Nonetheless, for adult-onset acute spondylolysis with bone edema, conservative therapy is probably as effective as during adolescence with regard to achievement of bone union.…”
Section: Discussionmentioning
confidence: 99%
“…Because most patients are referred to our hospital by their primary care physicians for a comprehensive adolescent examination, MRI is used in all cases, except those involving obvious trauma, as it has previously been reported to be useful for early diagnosis and prevention of missed lesions [ 4 , 9 ]. Furthermore, in cases where MRI shows high-intensity changes within the pedicle, CT is performed because bone fusion rates in lumbar spondylolysis vary greatly depending on the stage (e.g., 94% in early stage, 80% in progressive stage, and 0% in terminal stage), and stage diagnosis can only be performed by CT, as many reports have shown [ 1 , 3 , 5 , 7 , 8 , 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…stress reaction have been proposed as a preliminary stage of fracture when no fracture line is observed on CT but intensity changes are apparent on MRI. In these cases, the bone healing rate has been reported to be nearly 100% [1,[5][6][7][8]. However, no detailed studies of pre-lysis-stage lesions have been reported.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation